2016
DOI: 10.3390/molecules21081088
|View full text |Cite
|
Sign up to set email alerts
|

Copper Ion Attenuated the Antiproliferative Activity of Di-2-pyridylhydrazone Dithiocarbamate Derivative; However, There Was a Lack of Correlation between ROS Generation and Antiproliferative Activity

Abstract: Abstract:The use of chelators for cancer treatment has been an alternative option. Dithiocarbamates have recently attracted considerable attention owning to their diverse biological activities; thus, the preparation of new dithiocarbamate derivatives with improved antitumor activity and selectivity as well as probing the underlying molecular mechanism are required. In this study, di-2-pyridylhydrazone dithiocarbamate S-propionic acid (DpdtpA) and its copper complex were prepared and characterized, and its anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 48 publications
(60 reference statements)
3
28
0
Order By: Relevance
“…In the present study, we demonstrated that copper ion significantly attenuated antiproliferative activity of DpdtaA against HepG2 cells (Fig. 2), which was similar to that previously reported for DpdtpA (19). The two dithiocarbamtes (DpdtaA and DpdtpA) have similar structures, only one carbon difference, their antiproliferative effect against HepG2 cells was also similar, but upon chelation of copper, the propionic acid thiol ester showed greater fold decrease than acetate in antiproliferation.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In the present study, we demonstrated that copper ion significantly attenuated antiproliferative activity of DpdtaA against HepG2 cells (Fig. 2), which was similar to that previously reported for DpdtpA (19). The two dithiocarbamtes (DpdtaA and DpdtpA) have similar structures, only one carbon difference, their antiproliferative effect against HepG2 cells was also similar, but upon chelation of copper, the propionic acid thiol ester showed greater fold decrease than acetate in antiproliferation.…”
Section: Discussionsupporting
confidence: 90%
“…As shown in Fig. 2A-D, the DpdtaA caused rounded HepG2 cells, but the addition of copper ion significantly attenuated the action, showing an antagonistic effect as we previously reported (19). We speculated that the 'antagonistic effect' might stem from a new species which was confirmed at DpdtaA/Cu =1:1 ratio in composition by spectral titration (data not shown).…”
Section: Preparation and Proliferation Inhibition Of Dpdtaasupporting
confidence: 67%
See 2 more Smart Citations
“…In conclusion our search for this complex might produce more specific anticancer effects is ongoing [71] and copper is an essential element for cell growth many drugs used in clinical practice and has ability and display cytotoxicity [72] . Acryl amide-induced DNA genotoxicity, adduction and mutagenesis Direct interaction of acrylamide with DNA through Michael-type addition reaction is considerably slow [73] , where the interaction of glycidamide with DNA through Michael-type addition is relatively fast as concluded from the semi-empirical MOPAC calculations [74] . The reaction mechanism was suggested to proceed via a preliminary nucleophilic attack of the guanine NH group onto the acrylamide double bond or oxirane ring in glycidamide resulting in the formation of 7-(2-carbamoyl-2-hydroxyethyl)-guanine (N7-GA-Gua), figure 8.…”
Section: Anticancer Activity Using In-vitro Cytotoxic Assaymentioning
confidence: 99%